Automatic vehicle accident detection and alerting notification using internet of things - Savani, Vijay; Pandya, Viranchi; Senghani, Dhairya; Nahta, Shreya; Agrawal, Risheen (International Journal of Informatics and Communication Technology (IJ-ICT), 2025)
Immigrants in developing countries have indirectly encouraged increased automobile use, leading to a strong association between automobile accidents and their victims. However, recent technological developments, especially artificial intelligence and electronics, seem promising in overcoming these risks. This research paper focuses on complex systems developed using internet of things (IoT) technology. The system integrates various components such as micro controller, radio frequency identification (RFID) card reader for license validation, liquid crystal display (LCD), Ultrasonic sensor for interference, measuring device and global positioning system (GPS) unit. Additionally, the system has a simple mail transfer protocol (SMTP) server that can send timely email alerts to emergency responds and log email addresses for real-time emergency detection. This facilitates rapid response and emergency rescue, thereby reduces the risk of accidents and increases overall safety.